Analysis of inductive powering harvesting circuit - Ma , Li Ya; Md Ralib, Aliza Aini; Jamil, Nadira; Khan, Sheroz; Alam, A. H. M. Zahirul; Nordin, Anis Nurashikin (2010)
The use of implanted devices for biomedical applications is on the rise. As reliability and longevity of the power source is an issue of concern so research is underway for using other means of energy sources such as solar, vibrations and inductive coupling, The inductive coupling providing a noninvasive means of energy source, and is hence considered the most reliable contender. In this case the primary coil is wound on an external mount while the secondary (few turns) is embedded on implanted bed. A theoretical and simulation of inductive coupling is done using MATLAB© exploring its frequency response.